2021
DOI: 10.21203/rs.3.rs-244923/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diverse recruitment to a taxonomically structured global atmospheric microbiota

Abstract: Atmospheric transport is critical to dispersal of microorganisms between habitats and this underpins resilience in terrestrial and marine ecosystems globally. A key unresolved question is whether microorganisms assemble to form a taxonomically distinct, geographically variable, and functionally adapted atmospheric microbiota. Here we characterised inter-continental patterns of microbial taxonomic and functional diversity in air within and above the atmospheric boundary layer and in underlying soils for 596 glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 71 publications
(80 reference statements)
1
2
0
Order By: Relevance
“…Their samples may also have been affected by postdepositional processes, such as selection and cell growth. Contrary, the number of ASVs in the air samples collected in spring and summer in this study closely resembled what had previously been reported in the Arctic ( Cuthbertson et al, 2017 ; Šantl-Temkiv et al, 2018 ; Archer et al, 2021 ). Altogether, our results reflect the pristine nature of the Arctic atmospheric environment, characterized by the dilution and decay during long-range transport, few local sources, as well as scarce human presence and activity which together result in low bacterial diversity and abundance.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Their samples may also have been affected by postdepositional processes, such as selection and cell growth. Contrary, the number of ASVs in the air samples collected in spring and summer in this study closely resembled what had previously been reported in the Arctic ( Cuthbertson et al, 2017 ; Šantl-Temkiv et al, 2018 ; Archer et al, 2021 ). Altogether, our results reflect the pristine nature of the Arctic atmospheric environment, characterized by the dilution and decay during long-range transport, few local sources, as well as scarce human presence and activity which together result in low bacterial diversity and abundance.…”
Section: Resultssupporting
confidence: 90%
“…To fully appreciate the processes involved in cloud and ice formation mediated by bioaerosols we must first obtain data on the quantity, diversity, and activity of the aerosolized microorganisms. Recent studies have addressed these questions mostly in temperate regions ( Bowers et al, 2009 ; Temkiv et al, 2012 ; DeLeon-Rodriguez et al, 2013 ; Klein et al, 2016 ; Amato et al, 2017 ; Archer et al, 2021 ). A few studies have investigated these questions in the low and the high Arctic ( Harding et al, 2011 ; Cuthbertson et al, 2017 ; Šantl-Temkiv et al, 2018 ; Tignat-Perrier et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Contamination can also derive from naturally dispersing microbes in aerosols. The atmosphere ensures the connectivity of many ecosystems on Earth by facilitating dispersal even at very long distances ( 27 29 ). Intrinsic microbial properties, including size, shape, resistance to desiccation and UV radiation, and even mechanisms to cope with long-term starvation ( 30 ), influence dispersal, but so do local meteorological conditions.…”
Section: Introductionmentioning
confidence: 99%